Factors that influencing duration time for recreation activities of recreationist at forest trail of Ayer Hitam Forest Reserve - Harun, Nor Hazimah (2018)
Ayer Hitam Forest Reserve (AHFR) is a reserve forest that should be protected from any form of activities. However, the issue of public encroachment to conduct the recreation activities had created a conflict between forest conservation and public health. These recreation activities gave the negative impacts to environmental issue such soil compaction, habitat fragmentation, trampling and wildlife disturbance (noise). This study aims to investigate the factors that influence recreationist spend time on recreation activities to this forest. A set of questionnaires was given to 300 of visitors at AHFR. The location of collecting data is located at entrance near Taman Wawasan, Puchong. Regression analysis was used to determine the factors that had influencing the presence of recreationist to the forest. The population of recreationist is diverse from different background of races, religion and education level from the data of the survey collected. Result from the regression analysis, the R2 of model summary was 0.094 and standard error was 0.089. The result shown that push factors influence the recreationist come to AHFR for recreation due as a result of recreationist self- behaviours and psychology to fulfill their own desire. Thus, the equation of regression model can be express as Y=−0.745+ 0.495X1.This study also determined the best mechanism for conservation of AHFR Trails. The suggestion they given are based on education, campaign, smoking prohibition, law and regulation and leaves it by own nature.